Smart Farm Hydroponics berbasis IOT dengan NodeMCU ESP8266 - Rahmad Doni; Iwan Fitrianto Rahmad (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
The development of information technology is increasing rapidly from time to time, information technology can be felt directly by humans and has experienced significant changes in several sectors of life. One form of progress in the field of information technology is the Internet of Things (IoT) platform. Agriculture is an important sector for people's lives. Hydroponics is a method in agriculture that can cultivate plants without the need for land, but uses water and nutrient solutions as a planting medium. This hydroponic cultivation has many advantages including more practical maintenance and more controlled pest disturbances, does not depend on natural conditions, and can be done on limited land. To optimize agricultural products, farmers need to get nutritional conditions, solution pH and temperature in real time to be able to make the right decisions for what crops to plant. The process of decreasing the temperature from 360 Celsius to 340 Celsius lasts ± 3 minutes. And the provision of plant nutrition is carried out by order through the Blynk application.